Пенсійне забезпечення в українських губерніях у ХІХ – на початку ХХ ст.: загальноросійське законодавство та місцеві особливості - Мазур, В. (Український історичний журнал, 2022)
Метою статті є дослідження розвитку пенсійного забезпечення в українських
губерніях Російської імперії упродовж ХІХ – початку ХХ ст. Методологія передбачає
використання принципів історизму, системності та науковості. Ключову роль відіграли
історико-порівняльний метод, який уможливив проведення паралелей між загальнодержавним
законодавством та регіональними прецедентами, суміжні методи юридичних наук і
соціології, зважаючи на вивчення правового поля та суспільних відносин. Наукову новизну
формує об’ємне джерелознавче підґрунтя, розгляд пенсійного забезпечення як результату
закономірної еволюції ставлення держави до різних професійних категорій і впливу кон’юнктурних
чинників, які зумовлювали надмірний ріст витрат та незавершеність реформаційних
процесів. Мало- і невідомі приклади, які стосувалися українських губерній, забезпечили
створення комплексної картини і виявлення низки негативних явищ. Висновки. Починаючи
із кінця XVIII ст., Російська імперія почала проводити цілеспрямовану політику задля належного
соціального забезпечення військовослужбовців та чиновників. Започатковане у цей
період заохочення за вислугу років поступово набуло форми масових пенсійних виплат, які
нерівномірно розподілялися між різними категоріями населення, з деформованими проявами
привілейованого становища керівних кадрів, окремими відомчими касами, підвищеними
платежами того. Український контекст вирізнявся більшою увагою до прикордонних територій
та правобережних губерній, власними проектами великих міст (Київ, Одеса, Харків),
масштабністю відповідної діяльності земських органів. The purpose of the article is to study the development of pension provision in the
Ukrainian provinces of the Russian Empire during the 19th and early 20th centuries. The methodology
involves the use of the principles of historicism, systematicity and scientificity. A key role
was played by the historical-comparative method, which made it possible to draw parallels between
national legislation and regional precedents, related methods of legal sciences and sociology, taking
into account the study of the legal field and social relations. The scientific novelty is formed by
the extensive jerelogical basis, the examination of pension security as a result of the legal evolution
of the attitude of the state to different professional categories and the influence of conjunctural
factors, which caused a significant growth of costs and incompleteness of the reform processes.
Little- and unknown examples, which concerned the Ukrainian provinces, ensured the creation
of a comprehensive picture and the identification of negative phenomena. Conclusions. Starting
from the end of the 18th century. The Russian Empire began to implement a purposeful policy
for the proper social security of servicemen and officials. The incentive for long service, initiated
during this period, gradually took the form of massive pension payments, which were unevenly
distributed among different categories of the population, with deformed manifestations of the
privileged position of managerial personnel, separate departmental cash registers, and increased
payments. The Ukrainian context was distinguished by greater attention to border territories
and right-bank provinces, own projects of large cities (Kyiv, Odesa, Kharkiv), and the scale of
the relevant activities of zemstvo bodies. At the beginning of the 20th century it became more
and more difficult to pay pensions from the budget, and in conditions of deliberate inhibition
of pension reform projects, the situation became more and more complicated (often the criticism
of these projects was fair). At the same time, the majority of the population (peasants, workers)
remained unprotected, and the lower ranks often received monthly payments at the level of several
rubles. In the Ukrainian provinces, more attention, taking into account strategic factors, was
paid to certain categories of the military (Black Sea Fleet, border territories, defense of Sevastopol
during the Crimean War) or civilian officials, for example, as part of their encouragement to serve
on the Right Bank. Gradually, from the end of the 1860s, and mainly at the end of the 1880s,
the initiative of individual zemstvos allowed them to create their own pension funds, and the
financial capabilities of large cities ensured limited payments to their own employees.